Investment opportunities in post-conflict countries how can post-conflict countries attract foreign direct investment : the case of Syria - Abdulhalim, Najah (My University, 2022)
Tarih boyunca çok sayıda ülke uzun ya da kısa süren savaşlardan etkilenmiştir. Bu çatışmalar sadece siyasi istikrarsızlık ve belirsizliğe değil, diğer olumsuz sonuçlara da yol açmaktadır. Buna ek olarak, çok sayıda ekonomik soruna neden olur ve bazı durumlarda gelişme ve genişleme çarkını tamamen durdurur. Çatışma sonrası bir ülke olarak Suriye'ye odaklanan bu makalede, çatışmanın Suriye ekonomisi üzerindeki etkileri incelenmektedir. Araştırmam sırasında, Suriye'nin rehabilitasyonu ve yeniden inşası sürecinde önemli bir rol oynayan doğrudan yabancı yatırımı cezbetmek için verimli bir strateji bulmaya çalıştım. En etkili stratejiyi belirlemek için, ekonominin ve toplumun en önemli yönlerine ışık tutmak için bu çalışmanın Suriye ekonomisinin çatışma öncesi ve sırasındaki yönlerini araştırmak ve değerlendirmek gerekiyordu. Suriye'ye benzeyen diğer bazı ülkelerdeki durumları analiz ederek, siyasi huzursuzluk ile yavaş ekonomik büyüme arasındaki bağlantıyı inceleyebildim. son olarak, şu anda Suriye'de yürütülmekte olan çeşitli kalkınma girişimleri için gerekli fonları elde etmenin bir yolu olarak bir finansal aracın oluşturulmasını teşvik eden bir öneride bulunuyorum. Bu Etki geliştirme tahvilini kullanarak uluslararası yatırımcıları cezbedebileceğiz.

Throughout history, a great number of countries have been affected by wars that lasted for either a long or a short period of time. These conflicts not only result in political instability and uncertainty but also in other negative consequences. In addition to this, it causes a multitude of economic issues, and in some instances, it completely stops the wheel of development and expansion in its tracks. The impacts of the conflict on Syria's economy are examined in this article, which focuses on Syria as a post-conflict country. In the course of my research, I tried to come up with a productive strategy to entice direct foreign investment, which plays a significant part in the process of rehabilitating and rebuilding Syria. In order to identify the most effective strategy, it was necessary for this study to investigate and assess the aspects of the Syrian economy both before and during the conflict in order to shed light on the aspects of the economy and society that are most significant. By analyzing the situations in a number of other countries that are analogous to Syria, I was able to study the connection between political unrest and slow economic growth. lastly, I put forward a suggestion that promotes the creation of a financial instrument as a means of obtaining the necessary funds for a variety of development initiatives that are now underway inside Syria. We will be able to lure investors internationally using this Impact development bond.
Keywords: Community Development; Development Impact Bond; Doğrudan yabancı yatırım; Early Economic Recovery; Erken Ekonomik İyileşme; Etki Yatırımı; Finance; Impact Investing; Kalkınma Etkisi Tahvil; Maliye; Mülteci Etki Tahvil; Non-governmental Organization; Refugee Impact Bond; Sivil toplum örgütü Foreign Direct Investment; Topluluk Geliştirme